Filling knowledge gaps for the State of Paraná, Brazil: Bats (Mammalia, Chiroptera) of Palotina municipality - Batista & José Marcelo Rocha Aranha, Sara Cristina (Acta Biológica Paranaense, 2017)
<htm>Filling knowledge gaps for the State of Paraná, Brazil: Bats (Mammalia, Chiroptera) of Palotina municipality </htm>